Zinc deficiency impairs axonal regeneration and functional recovery after spinal cord injury by modulating macrophage polarization via NF-κB pathway - Kijima, Ken; Ono, Gentaro; Kobayakawa, Kazu; Saiwai, Hirokazu; Hara, Masamitsu; Yoshizaki, Shingo; Yokota, Kazuya; Saito, Takeyuki; Tamaru, Tetsuya; Iura, Hirotaka; Haruta, Yohei; Kitade, Kazuki; et al. (Frontiers in Immunology, 2023)
Background: Spinal cord injury (SCI) is a devastating disease that results in permanent paralysis.Currently, there is no effective treatment for SCI, and it is important to identify factors that can provide therapeutic intervention during the course of the disease. Zinc, an essential trace element, has attracted attention as a regulator of inflammatory responses. In this study, we investigated the effect of zinc status on the SCI pathology and whether or not zinc could be a potential therapeutic target.We created experimental mouse models with three different serum zinc concentration by changing the zinc content of the diet. After inducing contusion injury to the spinal cord of three mouse models, we assessed inflammation, apoptosis, demyelination, axonal regeneration, and the number of nuclear translocations of NF-κB in macrophages by using qPCR and immunostaining. In addition, macrophages in the injured spinal cord of these mouse models were isolated by flow cytometry, and their intracellular zinc concentration level and gene expression were examined. Functional recovery was assessed using the open field motor score, a foot print analysis, and a grid walk test. Statistical analysis was performed using Wilcoxon rank-sum test and ANOVA with the Tukey-Kramer test.In macrophages after SCI, zinc deficiency promoted nuclear translocation of NF-κB, polarization to pro-inflammatory like phenotype and expression of pro-inflammatory cytokines. The inflammatory response exacerbated by zinc deficiency led to worsening motor function by inducing more apoptosis of oligodendrocytes and demyelination and inhibiting axonal regeneration in the lesion site compared to the normal zinc condition. Furthermore, zinc supplementation after SCI attenuated these zinc-deficiency-induced series of responses and improved motor function.We demonstrated that zinc affected axonal regeneration and motor functional recovery after SCI by negatively regulating NF-κB activity and the subsequent inflammatory response in macrophages. Our findings suggest that zinc supplementation after SCI may be a novel therapeutic strategy for SCI.